VALUABLE ORIENTATIONS AND MORAL ORIENTATION OF STUDENTS - S. I. Nekrasov (Naučnyj Vestnik MGTU GA, 2016)
The article is devoted to problems of formation of the valuable sphere of youth in the university community. It represents empirical analysis of the dynamics of value orientation of students in the period of 2005- 2013 as exemplified by the students of Moscow state university of railway engineering. The basic meaning of life orientation of young people, reflecting the positive and negative trends in their development. Particular attention is paid to the specifics of behavioral strategies for students, which are based on moral and ethical installation.